The Use Of Euphemism In Jimmy O. Yang Stand Up Comedy (Conference on English Language Teaching, 2023)
Euphemism is a polite utterance used to replace terms that are unlikely to be desired by the speaker since it might cause confusion for both the speaker and the listeners. The purpose of this research is to look into the functions of euphemism in Jimmy O Yang's stand-up comedy. The data for this study was gathered from two videos posted around 2022 by the YouTube channel laugh society. Burridge's (2012) theory of the euphemism function was employed to classify the data in this study. According to the findings of this study, there are five functions of euphemism: uplifting euphemism, ludic euphemism, underhand euphemism, provocative euphemism, and protective euphemism.